Flexible bronchoscopy in children: complications and predictive factors - Başaran, Ayşen; Başaran, Abdurrahman Erdem; Bankoğlu Parlak, Betül; Aycan, İlker Öngüç; Bingöl, Ayşen (The Turkish Journal of Pediatrics, 2025)
Background. Although flexible bronchoscopy (FB) is frequently performed in children, there is limited information on the potential complications and risk factors. In this study we aimed to evaluate the complications associated with pediatric FB and identify predictors of these complications.Methods. Patients aged 0-18 years who underwent FB at the Akdeniz University Pediatric Pulmonology Department between February 1, 2015 and June 30, 2023 were included in the study. We retrospectively recorded the patients’ demographic data, known diseases, pulmonary function test results, chest computed tomography findings, bronchoscopy time/indication/route/findings, vital signs, minor and major complications associated with the FB procedure, post-procedure intensive care unit admission, procedure and sedation durations, and American Society of Anesthesiologists physical status (ASA-PS) classification, Mallampati score and anticipated need for post-procedural intensive care as evaluated in the pre-procedure anesthesiology consultation.Results. The study included a total of 292 patients; 157 (53.8%) girls and 135 boys, with a mean age of 9.9±4.8 years. There were a total of 55 FB-related complications (18.8%), 19 major (6.5%) and 36 minor (12.3%), and 10 patients (3.4%) required intensive care unit admission due to the procedure. The most common complication was hypoxia (11.3%). Patient age, height, anticipated need for intensive care, and baseline oxygen saturation values were significant predictors of the development of bronchoscopy-related complications, while patient age, baseline diastolic blood pressure, anticipated need for intensive care, and route of insertion were predictors of major complications after bronchoscopy. ASA-PS score, pulmonary function test values, and procedure/sedation durations had no effect on the development of complications.Conclusion. Although FB is a fairly safe diagnostic method in children, extra caution regarding possible complications is warranted in young children, when using the nasal route of insertion, or if the patient is evaluated as high-risk in the pre-procedure assessment performed by the anesthesiologist.
Keywords: flexible bronchoscopy; complication; laryngeal mask; pediatrics; anesthesia